RHETORICAL PROBLEMS OF INDONESIAN RESEARCH ARTICLE RESULTS AND DISCUSSION IN THE HISTORY AND LAW DISCIPLINES - Warsidi, Warsidi; Adnan, Zifirdaus; Maniam, Vegneskumar (LLT Journal: A Journal on Language and Language Teaching, 2025)
The number of rhetorical studies of research articles (RAs) using a genre approach has increased greatly. However, studies on this area in Indonesian research articles (RAs) published in accredited journals are still limited. None has investigated the rhetorical structures of Indonesian History and Law research article results and discussions (RARDs) published in Indonesian accredited journals. Thus, the present study aims to analyse them rhetorically using English rhetorical models, one is from Tessuto (2015) and the other one is from Hopkins and Dudley-Evans (1988). The reason for employing these models is to determine whether the models could represent the rhetorical structure of the present data sets. These models were alternately tested against both data sets. The results showed that the rhetorical structures of both Indonesian History and Law RARDs are different from those presented in the English-tested models, and the analysis results showed that the present data have their models. These differences indicate problems for Indonesian authors in these two selected disciplines when publishing RAs in reputable English journals. Thus, these findings may contribute to English for Academic Purposes (EAP) for teaching instruction for publishing RAs in reputable English journals for authors in the two disciplines.